Protection of Citizenship Status in National Law as a Human Right is Linked to Article 15 Paragraph 2 of the Universal Declaration of Human Rights - Rizal Agung Mufti; Tajul Arifin; Ine Fauzia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to analyse the protection of citizenship status in Indonesian national law as part of human rights, with a focus on the implementation of Article 15(2) of the Universal Declaration of Human Rights (UDHR), which prohibits arbitrary deprivation of citizenship. The method used is a normative approach by analysing the laws and regulations governing citizenship in Indonesia and comparing them with the international principles in the UDHR. The results show that although Indonesia has regulated citizenship as a protected right, there are challenges in the implementation of these protections, such as administrative problems of citizenship, dual citizenship, and non-transparent loss of citizenship. The contribution of this research is to provide insight into the importance of protecting citizenship as a human right in the context of national and international law, and to suggest reforms to the administration of citizenship in order to guarantee this right more effectively.